Analisis Putusan Pengadilan Yang Mengabulkan Tuntutan Praperadilan Tentang Tidak Sahnya Status Tersangka - Nahda, Nahda; , Muchammad Iksan, SH.MH; , Hartanto, SH.M.Hum (2016)
The study aims to analyze the legal basis for the court to decide it unlawful status of the suspect, legal efforts undertaken and the impact of pretrial ruling in law enforcement. The study used juridical empirical approach, this type of research predreskriptif conveniently Polrestabes Surabaya. The results of basic research law judge is Warrant Investigation No. 03/01/01/2015, January 12, 2015, BG instead of law enforcement and not to enter echelon. The impact investigator / law enforcement officers to be careful to set the status of suspects and the legal process that is based on the principle of simple, cheap, fast becoming a "complicated" with the expansion of pretrial object.